Nursing Home Cost Studies and Reimbursement Issues - Bishop, Christine E. (CENTERS for MEDICARE & MEDICAID SERVICES, 1980)
This review of nursing home cost function research shows that certain provider and service characteristics are systematically associated with differences in the average cost of care. This information can be used to group providers for reasonable cost related rate-setting or to adjust their rates or rate ceilings. However, relationships between average cost and such service characteristics as patient mix, service intensity, and quality of care have not been fully delineated. Therefore, econometric cost functions cannot yet provide rate-setters with predictions about the cost of the efficient provision of nursing home care appropriate to patient needs. In any case, the design of reimbursement systems must be founded not only on technical information but also on public policy goals for long-term care.